ANALISIS PROSES PENATAUSAHAAN BELANJA PADA PEMERINTAH DESA ONGKAW TIGA KECAMATAN SINONSAYANG MINAHASA SELATAN BERDASARKAN PERMENDAGRI NOMOR 113 TAHUN 2014 - Pakaja, Ridhwan Muhammad Isma’il; Tinangon, Jantje J.; Afandi, Dhullo (GOING CONCERN : JURNAL RISET AKUNTANSI, 2020)
Good village financial management is an important aspect in the success of village development and community welfare. Moreover, each year the funds allocated to each village have increased. Good village financial management is management that is in accordance with guidelines set by the government, which is contained in Permendagri Number 113 of 2014 concerning Village Financial Management. The purpose of this study is to analyze the adequacy of village financial management, especially in the process of expenditure administration organized by the Ongkaw Tiga Village Government. In this study, the type of data used is qualitative data, while for data sources using primary data, and the analytical method used is descriptive analysis method. Based on the results of the study, it was concluded that in the preparation of the RAB, filing employee expenditure, filing SPP on goods and services spending, filing SPP capital expenditure almost everything done by the Ongkaw Tiga village government can be said to be not complied with. After the evaluation, the factors that influence the non-compliance of the village government in carrying out the procedures for submitting village expenditures are the lack of knowledge and understanding of the village apparatus from the Village Head to the Implementing Officer on the rules imposed so that there are many errors in the preparation or preparation of these documents.Â